Het fin-de-siècle als vertoning - Krul, W. (BMGN - Low Countries Historical Review, 2002)
In their publication entitled 1900: Hoogtij van burgerlijke cultuur, the authors, Jan Bank and Maarten van Buuren, failed to pay adequate attention to the contrasts and differences that typified Dutch culture at the fin de siècle. The book therefore lacks analytical precision. The term 'bourgeois culture' should not have been applied in such an all-inclusive and unambiguous manner. This review is part of the discussion forum IJkpunt 1900.